2003
DOI: 10.1258/135763303321159639
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telepsychiatry measured using the Health of the Nation Outcome Scale and the Mental Health Inventory

Abstract: In a telepsychiatry project in rural Queensland, data were collected from 124 patients attending hospital and general practice facilities for mental health-care and then again at follow-up one year later. Thirty-two of the patients were dealt with using telepsychiatry. Two health status scales were used to measure effectiveness: the Health of the Nation Outcome Scale (HoNOS), administered by the practitioners; and the Mental Health Inventory (MHI), which was self-administered by the patients. There was a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…Kennedy and Yellowlees [12] examined clinical outcomes in the use of VC with 124 patients entering mental health treatment in rural Queensland, Australia. All patients were offered the option of being treated by a psychiatrist using a VC system at 128 kbps and 32 patients (3 of whom were diagnosed with psychotic disorders) chose the VC option.…”
Section: Resultsmentioning
confidence: 99%
“…Kennedy and Yellowlees [12] examined clinical outcomes in the use of VC with 124 patients entering mental health treatment in rural Queensland, Australia. All patients were offered the option of being treated by a psychiatrist using a VC system at 128 kbps and 32 patients (3 of whom were diagnosed with psychotic disorders) chose the VC option.…”
Section: Resultsmentioning
confidence: 99%
“…24, 25 Several early studies with small samples that used early technologies reported patient outcomes in terms of rates of hospitalization, 26 global assessment of functioning, 27 and general health status. 28 In a study of 495 outpatients with a variety of psychiatric disorders, O’Reilly and colleagues compared outcomes of those randomly assigned to consultation in person or by videoconferencing. 29 Both groups showed comparable decreases in general ratings of symptomatology and distress, levels of “caseness,” and rates of hospitalization and reported moderate satisfaction with care.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,[21][22][23][24] There has been only one previous report on the use of telepsychiatry for the assessment of emergency patients where the first contact with the psychiatrist was by teleconference. 25 That program found the use of telepsychiatry with patients referred to an acute psychiatric hospital unit was comparable to telepsychiatry programs with nonacute patients.…”
Section: Discussionmentioning
confidence: 99%